Green Bonds, Investor Attention and Stock Market Reaction: Evidence from ASEAN Countries - Aini, Andini Nurul; Sukmadilaga, Citra; Ghani, Erlane K. (International Journal of Energy Economics and Policy, 2023)
Green bonds offer investors the opportunity to align their investments with their values and contribute to positive social and environmental impacts. These bonds are a promising tool for channelling investment towards projects that are environmentally friendly and promote the transition to a low-carbon and sustainable economy. Arguably, they play an important role in the fight against climate change and the achievement of sustainable development goals. However, there are not many studies that have examined the impact of green bond issuance on stock market reactions. This study aims to examine the effect of green bond issuance on investor attention and the stock market using route analysis and the SEM-PLS method, either directly or through the inclusion of investor attention as an intervening variable. This study performed content analysis on the annual reports of publicly listed companies in five ASEAN countries over a period of five years. This study demonstrates that investors’ interest in green bonds increases proportionally to their issuance. However, green bond issuance does not significantly influence stock market reactions. In addition, the issuance of green bonds has had no discernible effect on the stock market's response as measured by investor attention. The findings in this study provide some insights on how green bond issuance can influence stock market reactions through investor attention. Investors can use these insights to make future investment decisions, particularly in ASEAN companies.